The role of audit information dissemination in curbing the contagion of tax noncompliance - Fauzan Misra; Rahmat Kurniawan (Faculty of Economics and Business, University of Muhammadiyah Malang, 2020)
Disclosure about tax evasion may trigger the contagion of such behavior. However, exposure to news about discovered misconduct can lead to deterrence as well. The economics-of-crime approach and social norm-based explanation suggest that exposure to news about evasion may influence the receiver of information to imitate such misconduct. In contrast, a Psychology-based explanation argues against contagion in taxpayers' misbehavior. This study aims to investigate the effect of disclosing evasion information by another taxpayer toward tax non-compliance and testing of the effectiveness of audit information dissemination to mitigate the contagion effect of such non-compliance that may be occurred. The research was conducted by an experimental approach with a 2 x 2 between-subjects design. The results show that when information about tax evasion is publicly disclosed, unaudited taxpayers tend to imitate such misbehavior. However, the contagion effect of non-compliance can be mitigated by the official announcement of tax audit information.